Factors affecting the implementation of acquired skills and knowledge presented to farmers at Denman Rural Training Centre in Gaborone agricultural region, Botswana - Terblanche, S.E. (Stephanus Esaias), 1940- (University of Pretoria, 2013)
Dissertation (MSc (Agricultural Extension))--University of Pretoria, 2006.